2007
DOI: 10.1007/s10494-007-9070-x
|View full text |Cite
|
Sign up to set email alerts
|

Generic Transport Aft-body Drag Reduction using Active Flow Control

Abstract: Active flow-separation control is an effective and efficient mean for drag reduction and unsteady load alleviation resulting from locally or massively separated flow. Such a situation occurs in configurations where the aerodynamic performance is of secondary importance to functionality. The performance of heavy transport helicopters and aeroplanes, having a large, and almost flat, aft loading ramp suffer from the poor aerodynamics of the aft body. Hence, a combined experimental and numerical investigation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The experimental activities conducted in these frameworks demonstrated that a significant drag reduction could be obtained over a wide range of angles of attack through the use of different flow control strategies. Similar results were found in the numerical/experimental study by Ben-Hamou et al (4) , which aimed to investigate the effect on drag reduction produced by piezo-fluidic actuators situated at the back-ramp lower corner of a generic transport helicopter fuselage.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The experimental activities conducted in these frameworks demonstrated that a significant drag reduction could be obtained over a wide range of angles of attack through the use of different flow control strategies. Similar results were found in the numerical/experimental study by Ben-Hamou et al (4) , which aimed to investigate the effect on drag reduction produced by piezo-fluidic actuators situated at the back-ramp lower corner of a generic transport helicopter fuselage.…”
Section: Introductionsupporting
confidence: 80%
“…The drag reduction value (of the order of 2%) obtained at cruise attitude using such passive devices, requiring very simple modification to existing helicopters, can be considered a useful result leading to a non-negligible benefit in terms of fuel saving. In fact, recent literature has shown that slightly higher values of drag reduction (an average of 10% of the baseline fuselage drag only) can be obtained by employing active flow control strategies as air-jet blowing actuators positioned at the back-ramp region (3,4) . However, it must noticed that this latter solution would produce apparent drawbacks on existing helicopters related to installation, power requirements and maintenance of such active actuators.…”
Section: Resultsmentioning
confidence: 99%
“…In the study [233,234] conducted to determine the flow conditions for optimal performance of a delta wing, an array of five autonomous piezoelectric actuators were mounted on the leading edge of the semispan delta wing. For the study on the drag reduction and unsteady load alleviation [235], resulting from the separated flow at the aft part of a generic part of the helicopter/transport plane body, twenty four individually operated, compact cavity controlled piezo-fluidic actuators were positioned around the ramp. With these actuators, a total drag reduction of 3%-11% was reported.…”
Section: Flow Control With Discrete Piezoelectric Actuatorsmentioning
confidence: 99%